Implementing a DVB-T/H Receiver on a Software-Defined Radio Platform - Yong Jiang; Wen Xu; Cyprian Grassmann (International Journal of Digital Multimedia Broadcasting)
Digital multimedia broadcasting is available in more and more countries with various forms. One of the most successful forms is Digital Video Broadcasting for Terrestrial (DVB-T), which has been deployed in most countries of the world for years. In order to bring the digital multimedia broadcasting services to battery-powered handheld receivers in a mobile environment, Digital Video Broadcasting for Handheld (DVB-H) has been formally adopted by ETSI. More advanced and complex digital multimedia broadcasting systems are under development, for example, the next generation of DVB-T, a.k.a. DVB-T2. Current commercial DVB-T/H receivers are usually built upon dedicated application-specific integrated circuits (ASICs). However, ASICs are not flexible for incoming evolved standards and less overall-area efficient since they cannot be efficiently reused and shared among different radio standards, when we integrate a DVB-T/H receiver into a mobile phone. This paper presents an example implementation of a DVB-T/H receiver on the prototype of Infineon Technologies' Software-Defined Radio (SDR) platform called MuSIC (Multiple SIMD Cores), which is a DSP-centered and accelerator-assisted architecture and aims at battery-powered mass-market handheld terminals.